PENGARUH KUALITAS SUMBER DAYA MANUSIA, MOTIVASI DAN KEPEMIMPINAN TERHADAP KINERJA PEMERIKSA FORENSIK - Fotuho Waruwu (Universitas Mitra Indonesia, 2020)
ABSTRACT This research aims to analyze the performance of forensic examiner Puslabfor Bareskrim Police by looking at factors of quality of human resources, motivation and leadership partially or simultaneously and variable that big influence in this research. Statistical test used is multiple regression analysis with SPSS program. The research method used is a questionnaire with a population of 78 employees. The statistical test of coefficient of determination that has a big influence on forensic examiner performance of Puslabfor Bareskrim Polri is 126.8% obtained from motivation variable.Keywords: Quality of Human Resources, Motivation, Leadership, Performance.